2022
DOI: 10.3390/jcm11092540
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and Neonatal Outcomes following COVID-19 Vaccination in Pregnancy

Abstract: COVID-19 infection imposes a risk for pregnant individuals and may lead to adverse maternal and obstetric outcomes. This is a retrospective cohort study of all women giving birth between March and July 2021 at a single tertiary center. Obstetric and neonatal outcomes were compared between vaccinated and non-vaccinated pregnant women with singleton pregnancies. Women with prior COVID-19 infection, multiple gestations and stillbirth were excluded from the study. Of 4708 women who delivered during the study perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 22 publications
3
37
0
Order By: Relevance
“…Moreover, the average birth weight of newborns delivered by unvaccinated women was similar to that of newborns delivered by vaccinated women; however, the birth weight increased after the second dose and even more after the third dose. As confirmed by previously published studies, no difference in gestational age and birth weight was observed between vaccinated and unvaccinated pregnant women (27)(28)(29)(30)(31).…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the average birth weight of newborns delivered by unvaccinated women was similar to that of newborns delivered by vaccinated women; however, the birth weight increased after the second dose and even more after the third dose. As confirmed by previously published studies, no difference in gestational age and birth weight was observed between vaccinated and unvaccinated pregnant women (27)(28)(29)(30)(31).…”
Section: Discussionsupporting
confidence: 85%
“…There have now been several large population studies that examine the impact of COVID-19 vaccination on birth outcomes. [19] , [20] , [45] , [65] , [66] , [67] , [107] , [108] , [109] , [110] , [111] Lower rates of very preterm birth (<32 weeks gestation) was observed in vaccinated pregnant people in Ontario, Canada (34% reduction) and Sweden (22% reduction), [67] but no difference was observed in Norway. [67] Several studies reported no association of vaccination status with preterm birth, stillbirth, small for gestational age, very low birth weight, infant mortality, or neonatal hospitalizations.…”
Section: Covid-19 Vaccination and Pregnancymentioning
confidence: 99%
“… [67] Several studies reported no association of vaccination status with preterm birth, stillbirth, small for gestational age, very low birth weight, infant mortality, or neonatal hospitalizations. [19] , [20] , [45] , [65] , [66] , [67] , [106] , [107] , [108] , [110] , [111] Two studies reported 40-43% reductions in the rate of stillbirth in vaccinated people and the effect remained even after adjusting for common cofactors. [20] , [110] Another reported a slight decrease in risk for NICU admission in babies born to people receiving at least one-dose compared to those born to unvaccinated people.…”
Section: Covid-19 Vaccination and Pregnancymentioning
confidence: 99%
“…1). [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Of the 15 studies, 2 case-control studies and 13 cohort studies reported on 90443 vaccinated pregnant women and 265063 unvaccinated pregnant women. The included studies reported data from six countries: Israel, UK, Romania, Canada, US, Sweden, and Norway (Table 1).…”
Section: Search Results and Basic Characteristicsmentioning
confidence: 99%
“…20,21 Nevertheless, several individual observational studies exploring the effects of COVID-19 vaccines on pregnancy and perinatal outcomes have included preterm birth, small for gestation (SGA), NICU admission and so on for neonatal outcomes. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Due to the importance of neonatal outcomes after maternal pregnancy, there is an immediate need for a systematic review and meta-analysis of published data to clarify differences in neonatal outcomes between COVID-19 vaccination during pregnancy and unvaccination during pregnancy.…”
Section: Introductionmentioning
confidence: 99%